Pelatihan Perencanaan dan Pengendalian Mutu Beton dengan Optimalisasi Potensi Material Lokal/Limbah Industri di SMK Negeri 2 Banjarbaru Kalimantan Selatan - Ratni Nurwidayati; Nursiah Chairunnisa; Ade Yuniati Pratiwi; Mariamah Mariamah; Anita Oktavia (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
SMK Negeri 2 Banjarbaru has two competencies from their expertise packages, the Construction and Property Business and Modeling Design and Building Information. However, the academic community lacks knowledge about the procedures for mixing normal concrete and concrete using local waste and the procedures for testing destructive and non-destructive concrete. One of the wastes used is fly ash. Tests for concrete quality control can be carried out by two methods: destructive and non-destructive tests. The destructive test is carried out with a compressive strength test and a tensile strength test of concrete/concrete splitting strength, while a non-destructive test is a hammer test. So that the solution offered is to provide training on planning and quality control of concrete by optimizing the potential of local materials/industrial waste. After the event, the academic community of SMKN 2 Banjarbaru has increased concerning normal concrete mixing and the use of local waste according to SNI standards and quality control of concrete testing in the field using destructive and non-destructive testing methods.